Epidemiological trends of dengue disease in Brazil (2000-2010): a systematic literature search and analysis. - Maria Glória Teixeira; João Bosco Siqueira; Germano L C Ferreira; Lucia Bricks; Graham Joint (Public Library of Science (PLoS), 2013)
A literature survey and analysis was conducted to describe the epidemiology of dengue disease in Brazil reported between 2000 and 2010. The protocol was registered on PROSPERO (CRD42011001826: http://www.crd.york.ac.uk/prospero/display_record.asp?ID=CRD42011001826). Between 31 July and 4 August 2011, the published literature was searched for epidemiological studies of dengue disease, using specific search strategies for each electronic database. A total of 714 relevant citations were identified, 51 of which fulfilled the inclusion criteria. The epidemiology of dengue disease in Brazil, in this period, was characterized by increases in the geographical spread and incidence of reported cases. The overall increase in dengue disease was accompanied by a rise in the proportion of severe cases. The epidemiological pattern of dengue disease in Brazil is complex and the changes observed during this review period are likely to have been influenced by multiple factors. Several gaps in epidemiological knowledge regarding dengue disease in Brazil were identified that provide avenues for future research, in particular, studies of regional differences, genotype evolution, and age-stratified seroprevalence.PROSPERO registration number: CRD42011001826.